Eksistensi Angklung Buncis Sawargi di Desa Manggungjaya Kecamatan Rajapolah Kabupaten Tasikmalaya - Rifki Taufik Faturahman; Arni Apriani; Wan Ridwan Husen (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Angklung Buncis Sawargi is one of the high-value traditional Sundanese cultural heritages in Manggungjaya Village, Rajapolah District, Tasikmalaya Regency. This study aims to analyze the existence of Angklung Buncis Sawargi amidst the social and cultural changes of the local community. This research uses a qualitative method with a descriptive approach, through observation, in-depth interviews, and documentation. The study finds that the existence of this art form is still preserved due to the support of the local community, the participation of younger generations, and innovations in performances, such as the integration of traditional and modern music elements. Additionally, the role of art groups like Angklung Buncis Sawargi in various traditional events, entertainment, and education plays a crucial part in maintaining the continuity of this art. The implications of this research highlight the importance of collaboration between the government, art communities, and the public in preserving traditional art as local cultural identity, while also encouraging its development to remain relevant in the modern era. This preservation effort is expected to make Angklung Buncis not only locally recognized but also nationally acknowledged as a cultural heritage.